SFM Fetal Therapy Practice Guidelines: Fetal Medical Therapy - Vikraman, Seneesh Kumar; Bhatt, Reema Kumar (Journal of Fetal Medicine, 2023)
Fetal medical therapy encompasses a wide range of pharmacological interventions aimed at preventing, treating, or ameliorating specific pathological conditions in the fetus. In contrast to fetal surgery, fetal medical interventions involve administering drugs either through transplacental transfer (maternal oral, intramuscular or intravenous injections) or direct administration to the fetus (intraumbilical, intraamniotic, intramuscular, intraperitoneal and intracardiac). The available interventions can be divided into four categories depending on the impact it has on fetal well-being and physiology, conditions amenable to medical therapy with established benefits, drugs with likely or potential benefits, maternal drug therapy with indirect fetal benefits, and drugs administered for nontherapeutic benefits. Careful selection of the cases, discussion under an institutional review board or a multidisciplinary team, strict adherence to standard guidelines and recommendations, and performance by physicians with adequate expertise are mandatory.
Keywords: fetal medical therapy; fetal cardiac arrhythmias; dexamethasone; betamethasone; congenital hypothyroid goiters; Congenital toxoplasmosis; fetal analgesia